Ozone pollution: a `hidden` environmental layer for athletes preparing for the Tokyo 2020 Olympic & Paralympics - Sandford, G. N.; Stellingwerff, T.; Koehle, M. S. (British Journal of Sports Medicine, 2021)
Environmental factors such as climate and pollution form a key part of major championship preparation. The Tokyo 2020 Olympic/Paralympic Games will present a unique combination of high thermal and ozone stressors. Japan has the highest levels of ozone in the Organisation for Economic Co-operation and Development; with annual peak values (65-73 ppb) aligning with the Olympic/Paralympic schedules (23 July to 5 September 2021).